Antibody‐mediated complement activation in pathology and protection. Issue 4 (6th April 2020) - Goldberg, Benjamin S; Ackerman, Margaret E
Abstract: Antibody‐dependent complement activity is associated not only with autoimmune morbidity, but also with antitumor efficacy. In infectious disease, both recombinant monoclonal antibodies and polyclonal antibodies generated in natural adaptive responses can mediate complement activity to protective, therapeutic or disease‐enhancing effect. Recent advances have contributed to the structural resolution of molecular complexes involved in antibody‐mediated complement activation, defining the avid nature of participating interactions and pointing to how antibody isotype, subclass, hinge flexibility, glycosylation state, amino acid sequence and the contextual nature of the cognate antigen/epitope are all factors that can determine complement activity through impact on antibody multimerization and subsequent recruitment of complement component 1q. Beyond the efficiency of activation, complement activation products interact with various cell types that mediate immune adherence, trafficking, immune education and innate functions. Similarly, depending on the anatomical location and extent of activation, complement can support homeostatic restoration or be leveraged by pathogens or neoplasms to enhance infection or promote tumorigenic microenvironments, respectively. Advances in means to suppress complement activation by intravenous immunoglobulin (IVIG), IVIG mimetics and complement‐intervening antibodies represent proven and promising exploratory therapeutic strategies, while antibody engineering has likewise offered frameworks to enhance, eliminate or isolate complement activation to interrogate in vivo mechanisms of action. Such strategies promise to support the optimization of antibody‐based drugs that are able to tackle emerging and difficult‐to‐treat diseases by improving our understanding of the synergistic and antagonistic relationships between antibody mechanisms mediated by Fc receptors, direct binding and the products of complement activation. Abstract : Determinants and outcomes of antibody‐mediated complement activation: this review discusses the factors specific to antibodies, antigenic targets, pathogen defenses and tissue microenvironments that determine the consequences of complement activation. Furthermore, it explores some approaches to capture these complexities in in vitro assays and screens of antibody‐mediated complement functions in host–neoplasm, host–graft/auto–host and host–pathogen interactions. Image from Diebolder CA, Beurskens FJ, de Jong RN, et al . Complement is activated by IgG hexamers assembled at the cell surface. Science 2014; 343: 1260–1263. Reprinted with permission from AAAS.